Odpowiedź :
Odpowiedź:
zadanie 3
a) 10x²y -5xy² +xy = 5(2x²y+xy²) + xy
b) 8x³y² +x²y² +6x²y³=( 2²x²y+xy)² +6x²y³
zadanie 1 .
a)
(√3x -1)(√3x +1)> 2 (4x -2)
(√3x)²+√3x -√3x -1 > 8x -4
3x -1 > 8x -4 |+1
3x >8x -3 |-8x
-5x > -3 | : -5
x> 3/5
x { znak nieskończoności - 4/5 }
b)
0.2x(3x-1) - 0,3x(2x-1) < 6(0,2x +1)
0,6x² - 0,2x - 0,6x² - 0,3 < 1,2x + 6
0,2x - 0,3 < 1,2x +6
0,2x < 1,2x +5,7
-x < 5,7
x < -5,7
x {znak nieskończoności , -5,6}
Zadanie 2
a)
(5x -4y)(3x-2y)=15x² -10xy -12xy -8y²= 15x²-24xy +8y²
dla x=4 y=√3
15x²-24xy +8y²= 15 × 4² - 24× 4 × √3 + 8 ×√3²= 15× 16 -96×√3 + 8×3 = 240 -96√3+24 = 264-96√3